2017
DOI: 10.1017/s0144686x17000277
|View full text |Cite
|
Sign up to set email alerts
|

‘All the corridors are the same’: a qualitative study of the orientation experiences and design preferences of UK older adults living in a communal retirement development

Abstract: Abstract:Environments need to be designed such that they support successful orientation for older adults and those with dementia who often experience marked difficulties in their orientation abilities. To better understand how environments can compensate for decreasing orientation skills, voice should be given directly to those experiencing dementia to describe how they find their way and to understand their design preferences. This study explored the navigational experiences and design preferences of older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…The users' opinions on design have also recently been expressed by residents of a retirement development, who reported that the repetitive design layout and interior finishes contributed towards increased feelings of disorientation (O'Malley, Innes, Muir & Wiener, 2018). Additionally, the importance of 'homely' environments has been communicated as a vital environmental consideration (Day, Carreon, & Stump, 2000;Innes, Kelly, & Dincarslan, 2011;O'Malley, Innes, Muir, & Wiener, 2018;Zavotka & Teaford, 1997). These studies demonstrate that older adults with memory difficulties can express their experiences on how they navigate within an environment and offer opinions regarding the design.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…The users' opinions on design have also recently been expressed by residents of a retirement development, who reported that the repetitive design layout and interior finishes contributed towards increased feelings of disorientation (O'Malley, Innes, Muir & Wiener, 2018). Additionally, the importance of 'homely' environments has been communicated as a vital environmental consideration (Day, Carreon, & Stump, 2000;Innes, Kelly, & Dincarslan, 2011;O'Malley, Innes, Muir, & Wiener, 2018;Zavotka & Teaford, 1997). These studies demonstrate that older adults with memory difficulties can express their experiences on how they navigate within an environment and offer opinions regarding the design.…”
Section: Introductionmentioning
confidence: 87%
“…Specific focus was on how they experienced a route through a retirement development as well as their design preferences of their ideal living environment, as well as their preferences for the specific test setting. The findings from this study will allow for comparisons between the views of residents of a retirement development (O'Malley, Innes, Muir & Wiener, 2018) and older adults who are unfamiliar with a retirement development (this study).…”
Section: Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the words of Marks and Findley (), signage should be “adequate but (not) overdone to the point of there being so many signs that people do not see them” (p. 17). Additionally, the repetition of design is a major reason for disorientation (O'Malley, Innes, Muir, & Wiener, ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%